Diversity Of Indicator Bacteria In FIVE PONDS AROUND Kanyakumari District, Tamilnadu. - G.J.JENILA.; G.MADHUSOODANAN PILLAI; C. RADHA KRISHNAN NAIR (International Journal of Pharma and Bio Sciences, 2011)
The present study attempts to understand the diversity of indicator bacteria in five ponds around Marthandam and Nagarcoil town Kanyakumari District, July-2010 to December-2010. Occurrence of bacterial indicators in water depicts the pollution status of lentic ecosystem. The current study is a quantitative appraisal of Total coliforms, Fecal coliforms, Faecal Streptococci, Salmonella and Shigella counts. Total coliforms varied from 187 to 42x103 cfu/ml, fecal coliforms varied from 13 to 42x102 cfu/ml Faecal Streptococci varied from 2 to 61x102 cfu/ml, Salmonella from 2 to 2.9x102 cfu/ml and Shigella from 7x102 to 91x102 cfu/ml. As per bureau of Indian standards (BIS), Total coliforms counts should be 1/100ml in drinking water and 10 cfu/ml in recreational waters all ponds were found to harbour huge bacteria load via surface run of as well as defication of people. Standards of coliforms even in waste water for disposal as per BIS (1991) should not exceed 5000/100ml. This situation posses public health and reveals that coliforms counts in the ponds exceed even the limits prescribed for waste water disposal which warrants urgent measures for protection of the lentic ecosystems and source water treatment.